Pengaruh Multiple Intelligences Terhadap Prestasi Belajar Mahasiswa:Studi pada Mahasiswa Jurusan Sejarah IKIP Budi Utomo Malang - Septa Rahadian; Arif Wahyu Hidayat (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2016)
This research aims to determine the effect of Multiple Intelligences toward learning achievement in college history and sociology department IKIP Budi Utomo Malang. The method used in this study is the experimental method kind of explanatory research. The data obtained from the analysis of Multiple Intelligences questionnaire and analyzed using multiple linear regression. From the results of this research showed no significant difference between linguistic intelligence, logic and intra personal on learning achievement college student history and sociology department IKIP Budi Utomo. From the analysis of the data obtained coefficient R2 of 0.079 indicates variable linguistic intelligence, logic and intrapersonal have an influence on the learning achievement of 7.9% while the remaining 92.1% is influenced by other variables not examined. Suggestions from this research are expected to party institution is willing to conduct training on making and writing papers or scientific work so that students are able to make posts or tasks properly. were all students majoring history and sociology department IKIP Budi Utomo Malang.